Al-Nabiy Al-Ummiy dalam Telaah Historis-Semiotik - Fauzan, Aris (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2018)
This article tries to reveal another meaning to the word al-nabiy al-ummiy in the context of historic-Sufistic. Among Indonesian mufassirs al-nabiy al-ummiy means less read and write, although there are other muslim scholars who understand that the Prophet Muhammad does not know how to read and write. Based on this latter view it becomes an apologetic argument that all the revelations revealed to the Prophet Muhammad are independently. There were not influenced by the previous traditions and religious cultures. To find the meaning beyond the conventional meaning above, the author tries to trace the historical background before and during Muhammad's time by using descriptive analytic-historical and sufistic. The result of this discussion of the author finds that beyond the common sense al-nabiy al-ummiy can be understood by: first, that Muhammad saw as the perfect person he became the source (babon), polecy (policy), and wisdom (wisdom) both vertical and horizontal among the people. Secondly, based on the historical reality of the proud Arab nation if it is attributed to the lineage of Mother's side, it affirms that the prophet Muhammad is an honorable man. Third, al-nabiy al-ummiy became one of the visions of Islam as a motherly religion that women should be honored and get their rights. Fourth, al-nabiy al-ummiy as proof that the prophet Muhammad gave strict laws against the mothers (of a husband) who can not be passed on to the children of his old wife.